Bilateral Parietal Cortex Damage Does Not Impair Associative Memory for Paired Stimuli - Berryhill, Marian E. (2009)
Recent neuroimaging and neuropsychological findings indicate that the posterior parietal cortex (PPC) plays an important, albeit undefined, role in episodic memory. Here we ask whether this region is specifically involved in associative aspects of episodic memory. Experiment 1 tested whether PPC damage affects the ability to learn and retrieve novel word-pair associations. Experiment 2 tested whether PPC damage affects the retrieval of object-location associations, in a spatial fan task. In both experiments, patients showed normal levels of associative memory. These findings demonstrated that PPC damage did not prevent association memory for verbal items. Finally Experiment 3 tested whether PPC damage affects memory for non-verbal audio-visual pairs. The patients performed with normal accuracy, but with significantly reduced confidence. These findings indicate that the PPC does not have a central role in association formation per se and instead, indicate that the PPC is involved in other aspects of episodic memory.